2010
DOI: 10.1080/02678290903564403
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the electro-optical properties of ferroelectric liquid crystals by doping ferroelectric nanoparticles

Abstract: The effects on the physical and electro-optical properties of ferroelectric liquid crystals (FLCs) after the doping of a dilute suspension of ferroelectric nanoparticles (BaTiO 3 ) have been studied. Due to the permanent electric dipole moments of the ferroelectric nanoparticles, the spontaneous polarisation of FLCs with low doping concentration was about twice that of pure FLCs, in addition to a significant improvement in the dielectric properties, the response time and the V-shaped switching in the chiral sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 17 publications
1
23
0
Order By: Relevance
“…These factors include selection of materials, size, type, concentration, intrinsic characteristic and mutual interaction between NPs and LCs. Low concentration of NPs are usually preferred to yield a more stable and even distribution on the LCs, which lowers the interaction forces between the LC and NPs [24]. The size of NPs should be of comparable with the LCs, which would not cause serious disruption in the orderly arrangement of LCs.…”
Section: Introductionmentioning
confidence: 99%
“…These factors include selection of materials, size, type, concentration, intrinsic characteristic and mutual interaction between NPs and LCs. Low concentration of NPs are usually preferred to yield a more stable and even distribution on the LCs, which lowers the interaction forces between the LC and NPs [24]. The size of NPs should be of comparable with the LCs, which would not cause serious disruption in the orderly arrangement of LCs.…”
Section: Introductionmentioning
confidence: 99%
“…There are only few papers on this topic [54,55] till now, but they point to a strong effect of the particles. Liang et al [54] reported on almost doubling of the spontaneous polarization, enhancement of dielectric properties and faster response time in a ferroelectric LC CS1024 (Chisso) doped with BaTiO 3 ($30 nm size) in a small concentration.…”
Section: Dielectric and Reorientational Properties Of Ferroelectric Lmentioning
confidence: 99%
“…There are only few papers on this topic [54,55] till now, but they point to a strong effect of the particles. Liang et al [54] reported on almost doubling of the spontaneous polarization, enhancement of dielectric properties and faster response time in a ferroelectric LC CS1024 (Chisso) doped with BaTiO 3 ($30 nm size) in a small concentration. Unlike them, Mikułko et al [55] observed only slightly lower spontaneous polarization and lower relative dielectric permittivity for the nanocomposite of BaTiO 3 ($30 nm size) in another ferroelectric LC LAHS9.…”
Section: Dielectric and Reorientational Properties Of Ferroelectric Lmentioning
confidence: 99%
“…Recent developments show the effects of doping ferroelectric BaTiO 3 nanoparticles on the electro-optical properties of ferroelectric liquid crystals [17]. Li et al [18] proposed a model to show the interaction between ZnO nanoparticles and FLC molecules surrounding them and Huang et al [19] explored the importance of adding ZnO nanocrystals into the SSFLCs by probing the molecular binding of FLC molecules.…”
Section: Introductionmentioning
confidence: 99%